Fundamentals of Islamic finance and banking - Habib, Syeda Fahmida (Chichester, West Sussex, United Kingdom : John Wiley & Sons, 2018)
A comprehensive and fully up-to-date introductory textbook to Islamic finance and banking Islamic finance and banking is being used increasingly globally-especially in the regions of Middle East and North Africa, South East and South Asia. To cater to the need of trained Islamic finance staff, a large number of Educational institutions are beginning to offer courses, majors and minors in Islamic finance and banking. The major challenge faced by these institutions are suitable textbooks for both undergrad and post-grad levels and especially with the relevant instructor resources (PPTs, test bank, practice activities and answer keys). Luckily, Fundamentals of Islamic Finance and Banking is here to cover the most important topics related to Islamic finance and banking (IF&B) that are relevant for students of business, finance and banking. -Offers an historical background of Islamic finance -Covers the principles of Sharia Law as pertinent to finance and banking -Provides in-depth discussion of the six key Islamic banking products: Murabaha, Mudaraba, Musharaka, Ijara, Salam and Istisna -Discusses the Islamic insurance (Takaful) -Gives an overview of Islamic investment, especially Sukuks -Concludes with the global standing of the Islamic Finance and Banking industry Would-be colleges and universities offering this subject as a course within their finance and/or banking program can't be without this invaluable guide.
Risks of Banks -- Generic and Specific to Islamic BanksGeneric Risks; Risks Specific to Islamic Banks; Financial Intermediation; The Definition of Financial Intermediation; Conventional Financial Intermediation; Islamic Financial Intermediation; Islamic Financial Intermediation Models; Distribution of Islamic Banking Products; Conventional versus Islamic Financial Intermediation; Balance Sheet of an Islamic Bank -- Sources and Uses of Funds by an Islamic Bank; Sources of Funds; Application of Funds; Contracts in Shariah Law; Contracts of Exchange in Shariah-Compliant Commerce and Finance
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Finance -- Religious aspects -- Islam; Finance -- Islamic countries; Banks and banking -- Religious aspects -- Islam; Banks and banking -- Islamic countries; Electronic books